Substituted 2-Phenacylbenzoxazole Difluoroboranes: Synthesis, Structure and Properties - Skotnicka, Agnieszka (Molecules, 2020)
Novel fluorescent dyes such as benzoxazole-boron complexes, bearing β-ketoiminate ligands, have been synthesized and characterized with a focus on the influence of a substituent on the basic photophysical properties. (1)H, (11)B, (13)C, (15)N, and (19)F nuclear magnetic resonance (NMR) spectra of substituted 2-phenacylbenzoxazole difluoroboranes have been recorded and discussed. It is worth mentioning that a high correlation coefficient was found between (15)N-NMR parameters and substituent constants. The photophysical properties of these new dyes have been investigated by fluorescence and ultraviolet-visible (UV-Vis) absorption spectroscopy. The geometry optimization, vibrational spectra, and the HOMO and LUMO energies were calculated based on density functional theory with the use of the B3LYP functional and 6-311++G(d,p) basis set.